Rapid Resolution of Vulvar Crohn's Disease With Ustekinumab - Stoleru, Gianna (ACG Case Rep J, 2020)
In the evaluation of patients with inflammatory bowel disease, assessment of extraintestinal manifestations of disease is integral to clinical management. The patient described in this case is a 24-year-old woman with a history of inflammatory colonic Crohn's disease (CD) who presented to the hospital with one week of vaginal pain and swelling. Initial assessment focused on infectious etiologies, though final diagnosis of vulvar CD was made on biopsy. Clinical course and treatment of vulvar CD are poorly defined in existing literature. This case highlights the multidisciplinary management of inflammatory bowel disease patients and successful treatment of a rare extraintestinal manifestation with anti-interleukin 12/23 therapy.